Kami in šintoistična kozmogonija - Milčinski, Maja (Studia mythologica Slavica, 1999)
The paper discusses the notion of kami, which reflects the basic Japanese way of considering nature, the land, deities and the people. The Japanese cosmogonic myths and the cosmic harmony of myriads of kami are presented as a contrast to the one absolute God in the monotheistic religions.
Keywords: filozofija religije; japonska filozofija; šintoizem; kamiji; kozmogonija; Japonska